Value of signal averaged electrocardiogram for prediction of successful coronary artery thrombolysis - Stajer, D; Rode, P (Cor et vasa, 1991)
In 60 patients with acute myocardial infarction (AMI) treated with brief i.v. infusion of streptokinase, signal averaged surface ECG as well as 24-hour ECG were recorded within the first 6 hours after admission and 5 to 10 days later. Results obtained from a group with presumed reperfusion (early plasma creatine kinase activity peak, cessation of pain, decrease in ST segment elevations, the appearance of "reperfusion arrhythmias"), were compared to those from patients with no reperfusion. The first recording showed a higher incidence of ventricular late potentials (VLP) in the group with reperfusion (77% vs. 44%, p less than 0.01), and a smaller difference in the incidence of complex ventricular arrhythmias (89% vs. 68%, p = 0.06). In the period between the two recordings, the incidence of VLP decreased in higher proportion in the same group (p less than 0.025). The incidence of complex ventricular arrhythmias was similar in both groups in the second recording. The authors conclude that complex ventricular arrhythmias following successful thrombolytic therapy occur together with "reperfusion VLPs", which are a better marker for successful thrombolysis in patients with AMI than a high grade of ventricular ectopic activity.
Keywords: trombolytická terapie; reperfuzní poškození myokardu; Electrocardiography; Male; Middle Aged; Myocardial Reperfusion Injury; Streptokinase; Aged; mužské pohlaví; srdeční arytmie; senioři; Arrhythmias, Cardiac; infarkt myokardu; Thrombolytic Therapy; lidé; ženské pohlaví; Humans; Electrocardiography, Ambulatory; Myocardial Infarction; elektrokardiografie ambulantní; Female; lidé středního věku; streptokinasa; elektrokardiografie